KECERDASAN SOSIAL DALAM PEMBELAJARAN KOOPERATIF PERSPEKTIF AL-QUR’AN - Ahmad Zain Sarnoto; Siti Maria Ulfa (Academy of Education Journal, 2021)
This study concluded that social intelligence is a person's ability to understand other people and care about the social environment. This is based on the two dimensions of social intelligence from the perspective of the Koran that the authors found, namely the feeling dimension (affective aspect) and the action dimension (psychomotic aspect). In the feeling dimension (affective aspect) consists of empathy and sincerity, while the action dimension (psychomotic realm) consists of helping, friendship, caring and communication. This means that the Qur'an describes the balance between habl ma'a Khaliqih and habl ma'a ikhwanih. Thus, this Quran-based cooperative learning model can help improve children's social intelligence. Cooperative learning is a learning model using a system of grouping students, who have different academic backgrounds, gender, race, or ethnicity (heterogeneous). Cooperative learning can form interpersonal skills because there are elements of working together, helping each other, helping out and discussing. This is based on the two indicators of cooperative learning in the perspective of the Qur'an that the author found, namely helping and deliberation. The approach used in this study is a qualitative approach. While the method used is a thematic interpretation method. The data collection technique used is through literature study